A aprendizagem da escrita da língua portuguesa como língua adicional para surdos - Marcon, Andréia Mendiola (2022)
We aim, in this research, to devote attention to the study of learning to write Portuguese as an additional language for the hearing-impaired. In this bias, we seek to answer the following guiding question: When dealing with the learning of the Portuguese language in its written modality which actors are involved and whose content needs to be taken into consideration for the immersion of the deaf subject in written culture? The proposal is based on the researcher's experiences with the hearing-impaired reality and on the lack of scientific production in the field of deaf education. With the problem outlined, we took Vygotsky's (1999) and Gombert's (2003) conception of learning as a theoretical framework to comprehend how these authors understand the concept of learning, especially about learning to write in a given language. The research establishes as a general objective to investigate how the concepts and assumptions of these authors can help to understand how those with impaired heating bring to consciousness the conceptual/linguistic system of writing in Portuguese, as a learning process. To guide the investigative path the following specific objectives were outlined: a) to recognize and analyze the research that is being carried out in the scientific scope, concerning the learning of writing in Portuguese by deaf people who speak Libras (Brazilian Sign Language); b) select theoretical concepts laborated and worked by both Vygotsky and Jean Émile Gombert, to show their interpretations about learning, especially the writing of a given language, to establish a dialogic relationship between authors and concepts; c) retake the concepts in Vygotsky and Gombert as a possibility in the learning of writing in the field of education for the deaf. Therefore, the research was guided by the contributions of the bibliographic research, since they allow a deeper theoretical reflection on the investigated theme. The research is qualitative. Our premise is that the concept of learning to write Portuguese as an additional language by the deaf, through a reflective and conscious process of the writing system, can contribute to the conceptual and linguistic development of additional writing. Some results showed that for the process of emancipation of the conceptual system of additional writing to occur, Libras must open the gates of emancipation and make the mediated inclusion of the additional writing system. For that, it is necessary to have a linguistic behavior in Libras that can constitute a pillar for the knowledge of additional writing. Thus, it sets in motion the metalinguistic process to bring to awareness the best conceptual and linguistic resources in writing situations.